Production of high concentrations of ethanol from inulin by simultaneous saccharification and fermentation using Aspergillus niger and Saccharomyces cerevisiae. - Ohta, K (1993)
Pure nonhydrolyzed inulin was directly converted to ethanol in a simultaneous saccharification and fermentation process. An inulinase-hyperproducing mutant, Aspergillus niger 817, was grown in a submerged culture at 30 degrees C for 5 days. The inulin-digestive liquid culture (150 ml) was supplemented with 45 g of inulin, 0.45 g of (NH4)2SO4, and 0.15 g of KH2PO4. The medium (pH 5.0) was inoculated with an ethanol-tolerant strain, Saccharomyces cerevisiae 1200, and fermentation was conducted at 30 degrees C. An additional 20 g of inulin was added to the culture after 15 h of fermentation. S. cerevisiae 1200 utilized 99% of the 65 g of inulin during the fermentation, and produced 20.4 and 21.0% (vol/vol) ethanol from chicory and dahlia inulins, respectively, within 3 days of fermentation. The maximum volumetric productivities of ethanol were 6.2 and 6.0 g/liter/h for chicory and dahlia inulins, respectively. The conversion efficiency of inulin to ethanol was 83 to 84% of the theoretical ethanol yield.